When a brand caught fire: the role of brand equity in product-harm crisis. Issue 7 (11th November 2014) - Rea, Brianna; J. Wang, Yong; Stoner, Jason
Abstract : Purpose: – The purpose of this study is to investigate differences in consumer reactions to high- versus low-equity brands in terms of consumer attitude toward the brand, involvement with the brand, company credibility and consumer purchase intentions. Design/methodology/approach: – Experimental procedure is conducted to test three hypotheses using 317 consumer participants. The experiment is carried out comparing a high-equity personal computer (PC) brand and a low-equity PC brand involved in product-harm crisis. Findings: – The results indicate that, in the case of product-harm crisis, negative consumer perceptions regardless of brand equity level; less negative perceptions for a high-equity brand than for a low-equity brand; and smaller loss in consumer perceptions for a high-equity brand than for a low-equity brand. Research limitations/implications: – The findings highlight the importance of brand equity in crisis management explained by covariation theory of attributions. Practical implications: – Although product-harm crisis is inevitable for many firms, continuous investment in brand equity can mitigate the negative consequences. Originality/value: – Product-harm crisis can pose serious consequences for firms on both financial and intangible dimensions. Given the occurrence of numerous product-harm crises involving both reputable and less known brands, it is important to consider potential influences of brand equity on consumer reactions to such crisis.